Dual energy metabolism of the Campylobacterota endosymbiont in the chemosynthetic snail Alviniconcha marisindica - Miyazaki, Junichi (ISME J, 2020)
Some deep-sea chemosynthetic invertebrates and their symbiotic bacteria can use molecular hydrogen (H(2)) as their energy source. However, how much the chemosynthetic holobiont (endosymbiont-host association) physiologically depends on H(2) oxidation has not yet been determined. Here, we demonstrate that the Campylobacterota endosymbionts of the gastropod Alviniconcha marisindica in the Kairei and Edmond fields (kAlv and eAlv populations, respectively) of the Indian Ocean, utilize H(2) in response to their physical and environmental H(2) conditions, although the 16S rRNA gene sequence of both the endosymbionts shared 99.6% identity. A thermodynamic calculation using in situ H(2) and hydrogen sulfide (H(2)S) concentrations indicated that chemosynthetic symbiosis could be supported by metabolic energy via H(2) oxidation, particularly for the kAlv holobiont. Metabolic activity measurements showed that both the living individuals and the gill tissues consumed H(2) and H(2)S at similar levels. Moreover, a combination of fluorescence in situ hybridization, quantitative transcript analyses, and enzymatic activity measurements showed that the kAlv endosymbiont expressed the genes and enzymes for both H(2)- and sulfur-oxidations. These results suggest that both H(2) and H(2)S could serve as the primary energy sources for the kAlv holobiont. The eAlv holobiont had the ability to utilize H(2), but the gene expression and enzyme activity for hydrogenases were much lower than for sulfur-oxidation enzymes. These results suggest that the energy acquisitions of A. marisindica holobionts are dependent on H(2)- and sulfur-oxidation in the H(2)-enriched Kairei field and that the mechanism of dual metabolism is controlled by the in situ H(2) concentration.